Users' Perspectives on mHealth Self-Management of Bipolar Disorder: Qualitative Focus Group Study - Switsers, Lise; Dauwe, Arthur; Vanhoudt, Anneleen; Van Dyck, Hilde; Lombaerts, Koen; Oldenburg, JFE (JMIR Publications, 2018)
BackgroundRecent research indicates that current mHealth apps for bipolar disorders (BDs) show crucial shortcomings. They lack important functionality, are of inconsistent quality, and are insufficiently evidence-based. mHealth apps need to be better adapted to the needs of users. The perspectives of adult service users with BD regarding mHealth apps have not been well investigated. ObjectiveThe objective of this study was to examine the needs and expectations of adults with BD regarding mHealth apps. MethodsTwo focus group sessions were organized in which patients' views on self-management and design and functionality of an mHealth app for BD were assessed. During session 1, four focus groups were organized to identify users' needs regarding support for self-management. Session 2 contained three cocreation focus groups. Through this method, the desired functionality and design were explored. ResultsParticipants indicated that they were in need of support in various ways. Not only support in psychoeducation, including daily routine, sleep pattern, maintaining social contacts, maintaining a healthy lifestyle, and avoidance of stimuli, was considered important for them but also gaining insight into their illness was found to be crucial. ConclusionsAccording to the participants, their illness-related information is a key factor in gaining insight into their mood pattern. Participants wanted a functional design that would increase daily use and prevent overstimulation. The results of this study should be taken into account when developing new mHealth apps.